Forum for the Transformation of Food Systems and the Reduction of Overweight and Obesity in Latin America and the Caribbean - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
FAO and IFPRI have identified a need for a space of exchange of knowledge and experience of experts from different sectors of public policy, academia, private sector and civil society, with expertise in the issues related to Food Systems and Obesity working in Latin America in order to help develop fact-based policy interventions to address the challenges of overweight and obesity in the region. The Forum for the Transformation of Food Systems and the Reduction of Overweight and Obesity in Latin America and the Caribbean was created with the objective of becoming such space, with interest of identifying the characteristics of the food systems that hinder the access to healthy foods by consumers, particularly from the poorest segments of the population, either due to the lack of physical availability and high prices of such foods, the supply of cheap and poor nutritive products or the inherent cultural or social conditions of the most vulnerable population groups, which make them live in unhealthy environments or choose unhealthy food patterns.